Internal thoracic artery harvesting without pleurotomy – does smaller injury mean a better outcome? - Nowicki, Rafał; Marczak, Jakub; Bankowski, Tomasz; Murmyło, Marcin; Bielicki, Grzegorz; Rachwalik, Maciej; Kustrzycki, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Introduction : The internal thoracic artery (ITA) remains the graft of choice for coronary artery bypass grafting (CABG). Harvesting the ITA without pleurotomy may be a desirable approach if the technique is proven to decrease morbidity and mortality and improve the economic result. The aim of the study was to evaluate the impact of different harvesting techniques on postoperative blood loss, transfusion requirements and duration of postoperative therapy. Material and methods : We carried out a prospective study that involved 115 patients who underwent on-pump CABG in our clinic. Patients were divided into two groups: those who underwent pleurotomy due to ITA harvesting (group A; n = 73) and the rest where pleura spearing technique was applied (group B; n = 42). Predicting factors for proposed end-points were assessed by stepwise forward regression. Results: Postoperative chest tube drainage (CTD) at the 12th and the 24th hour as well as the hemoglobin level did not differ statistically. Nonetheless, patients with pleurotomy required significantly more units of packed red blood cells (RBC), fresh frozen plasma (FFP) and packed platelets (PLT) than patients with intact pleural cavity (RBC = 0.94 ±1.4 vs. 0.5 ±0.9; p < 0.001; FFP = 0.6 ±1.5 vs. 0.4 ±1.1; p < 0.001; PLT = 0.3 ±1.5 vs. 0.1 ±0.8; p < 0.001). Regression analysis indicated that opening of the pleural cavity was a prediction factor for higher CTD at the 12th hour (β = 0.18; p = 0.03) and prolonged postoperative hospitalization (β = 0.17; p = 0.04). Group A patients were also found to require a longer intensive care unit (ICU) stay than those of group B (A: 1.5 ±1.0 vs. B: 1.3 ±0.6; p < 0.001). Conclusion : Spearing of pleura in the ITA harvesting procedure decreases morbidity and improves the economic result for patients qualified for on-pump CABG.